Fungsi Komunikasi Edukasi Manajemen Pariwisata Regional-Internasional Dengan Learning by Doing bagi Anggota Bhakti Wanita Ikopin (BWI) - Purnamawati, Ami (E-Coops-Day, 2024)
Fungsi Komunikasi Edukasi Manajemen Pariwisata Regional-Internasional Dengan Learning by Doing bagi Anggota Bhakti Wanita Ikopin (BWI) One of the instrumental communication functions is to educate. It means that the messages as well as the method conveyed are to make the receivers - the members of Bhakti Wanita Ikopin (BWI) - understand and practise them at once. For this activity, Communication of Regional – International Tourism Management becomes the main message. Because the purposes of the activity were to broaden knowledges and to enrich experiences of tourist destinations, accommodation, transportation system, communication system, culinary, and cultures, etc; they chose Singapore and Malaysia as their tourist destinations. In this case the writer determined to encourage the participants to have willing in managing the travelling activities independently without travel agent service. Using learning by doing or experiential learning method, the activity was initiated in two weeks by planning all elements, then conducting the travelling for a week, and last but not least evaluating the travelling program. During the whole activities, the participants were able to plan, and to implement all plannings pretty well not to mention having fun in every destination.